A very rare cause of the intra-abdominal bleeding - Ali Naki Yücesoy, (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Yücesoy AN. A very rare cause of the intra-abdominal bleeding. Turk J Gastroenterol 2019; 30(9): 846-7.